SEXUAL EDUCATION IN EARLY CHILDREN (BELIA: Early Childhood Education Papers, 2022)
The purpose of this study is to explain how sexual education in early childhood and to explain the supporting factors and inhibiting factors in providing sexual education to early childhood in the area of ​​RT.012/RW.05, Kel. Kalipancur, Kec. Ngaliyan. This type of research uses qualitative research methods, namely researchers describe a problem found in the field and the results of their findings and discussed in depth with existing theories. The sampling technique used in this research is snowball sampling. Snowball sampling technique is a data collection technique based on references from key informants to who are supporting informants and uses data analysis from the interactive technique proposed by Miles and Huberman with 4 stages, namely data collection, data reduction, data presentation, and drawing conclusions. From the results of this study, there are 4 aspects of providing sexual education to early childhood, namely 1). biological aspects 2). social aspects, 3). psychological aspects and 4). spiritual aspect. Supporting factors in providing sexual education for early childhood are the support and cooperation between family members and parenting seminars to increase knowledge in providing education to children, especially sexual education in early childhood. The inhibiting factor in sexual education in early childhood is the thought of some people who consider this education taboo and not suitable for their age and the existence of sites that provide information about this education that is not correct in providing information. Keywords: Society, Sexual Education, Early Childhood